Dissecting The Genomic Profile Of Persistently Infecting Oncolytic Newcastle Disease Virus (Ndv) From Cancer Rna-Seq Data - Ahmad, Umar Salisu (My University, 2021)
Newcastle disease virus (NDV) is an oncolytic virus with non-segmented negative single stranded ssRNA (−) genome of 15kb size. It contains six genes which encodes six major structural proteins arranged in the sequence order of 3’-NP-P-M-F-HN-L-5’. NDV selectively replicate and kills many different human cancer cells, however, it has been found to persistently infect a subset of bladder cancer cells that resist NDV-mediated oncolysis. Analysis of NDV genome (NDVpi) that persistently infecting the cancer cells revealed deletion and insertion regions in NP and M protein of the virus. In addition, genome truncations were observed at HN and L proteins regions. Thus, changes in nucleotide sequences of the viral genome may have significance impact on the development of persistence infection in bladder cancer cells. However, it is not clear how this mutational changes occurred to bring about persistence infection in bladder cancer cells.
Keywords: Newcastle disease virus genome; bladder cancer; RNA-Seq